Clustering Earthquake Event Points in the Southeast Asia Region using Agglomerative Hierarchical Clustering - Arifin, Adi (Sistemasi: Jurnal Sistem Informasi, 2023)
Earthquake is an inevitable and highly dangerous natural disaster due to its sudden and uncontrollable occurrence. Earthquakes frequently happen in the Southeast Asia region, resulting in infrastructure damage, loss of life, and economic disruption. Therefore, efforts should be made to mitigate earthquake risks, including the classification of earthquake data in the Southeast Asia region. The data used in this study were obtained from The Seismological Facility for the Advancement of Geoscience (SAGE), a facility funded by NSF and operated by the Incorporated Research Institutions for Seismology (IRIS). The study employed Agglomerative Hierarchical Clustering (AHC) to group the data into multiple clusters. The validity of the formed clusters was assessed using Silhouette Score Index (SSI), Davies Doublin Index (DBI), and Calinski Harabasz Index (CHI). The study involved two clustering processes, resulting in three clusters for the first clustering process aimed at creating new attributes, namely Area, and three clusters for the second clustering process aimed at identifying the types of earthquakes in the Southeast Asia region. These three formed clusters had SSI, DBI, and CHI values of 0.434353, 0.887791, and 3769.030146, respectively, indicating that AHC successfully classified the earthquake data. The findings of this research serve as a reference for further studies such as earthquake prediction and contribute to disaster mitigation strategies to enhance preparedness for future events.